Analysis and Monitoring of Land Subsidence Phenomena in Tambak Lorok, Semarang City Using the In-sar Method - Fadhila Tiara A; Rini Kusumawardani (Jurnal Teknik Sipil dan Perencanaan, 2024)
Rapid urbanization and infrastructure expansion in Semarang, particularly in the northern coastal areas, have led to significant land subsidence. Tambak Lorok, located in Tanjung Mas Sub-district, is among the affected areas, with key contributing factors including soft young alluvial soils, excessive groundwater extraction, infrastructure loads, coastal sediment dynamics, and tidal fluctuations. To understand the patterns and rates of land subsidence, this study employs the Interferometric Synthetic Aperture Radar (InSAR) method using the  Sentinel Application Platform (SNAP). The methodology involves the analysis of Sentinel-1A satellite imagery (2020–2024), Digital Elevation Model (DEM) mapping, and examination of changes in watershed (DAS) areas. Additional data were gathered through local community interviews and analysis of Google Maps and DEM data from 2018–2024. Long-term InSAR monitoring reveals that certain areas in North Semarang's coastal zone are subsidining at rates between -0.16 to -0.23 meters per year. Data validation was conducted through triangulation to ensure result accuracy. These findings highlight the need for more effective mitigation strategies, such as stricter groundwater management, adaptive infrastructure upgrades, and spatial planning that considers subsidence risks. Furthermore, remote sensing technology should be complemented with ground-based monitoring to ensure more accurate and data-driven mitigation strategies. The outcomes of this research are expected to serve as a basis for disaster mitigation and sustainable coastal spatial planning